2019
DOI: 10.1088/2053-1583/ab3beb
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of point defects in ultrathin layered 1T-PtSe 2

Abstract: Among two-dimensional (2D) transition metal dichalcogenides (TMDs), platinum diselenide (PtSe2) stands at a unique place in the sense that it undergoes a phase transition from type-II Dirac semimetal to indirect-gap semiconductor as thickness decreases. Defects in 2D TMDs are ubiquitous and play crucial roles in understanding and tuning electronic, optical, and magnetic properties. Here we investigate intrinsic point defects in ultrathin 1T-PtSe2 layers grown on mica through the chemical vapor transport (CVT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 67 publications
(117 reference statements)
11
72
2
Order By: Relevance
“…1b. Consistent with early scanning tunneling microscopy investigations 19 , we observe native Se and Pt vacancies in ultra-thin PtSe 2 films. The concentration of Pt vacancy defects is found to be~9 × 10 12 cm −2 (see Supplementary Note 2).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…1b. Consistent with early scanning tunneling microscopy investigations 19 , we observe native Se and Pt vacancies in ultra-thin PtSe 2 films. The concentration of Pt vacancy defects is found to be~9 × 10 12 cm −2 (see Supplementary Note 2).…”
Section: Resultssupporting
confidence: 90%
“…Motivated by direct observation of Pt vacancies in our transmission electron microscope images shown in Fig. 1b, their indirect inference from our charge transport measurements as well as earlier scanning tunneling microscopy studies 19 , we investigate electronic and magnetic properties of mono-and bilayer models of PtSe 2 with platinum vacancy defects by means of first-principles calculations. For the monolayer case, we find that a Pt vacancy defect in its fully spin-polarized configuration gives rise to a local magnetic moment of 4.00 μ B , which is localized mostly on the six selenium atoms neighboring to the missing Pt atom.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, recent reports have indicated that damage by the TEM electron beam can be a problematic issue for TMDs. [37][38][39] On the other hand, scanning tunnelling microscopy and spectroscopy (STM/STS) are non-destructive techniques, which can be used to map morphology and probe the electronic structure of samples [40][41][42][43] and, provided a conductive pathway can be established through the sample, do not require a transfer process.…”
Section: Introductionmentioning
confidence: 99%
“…Similar domains were observed by Zheng et al, and were interpreted as Se-rich antisite defects. 47,48 Aer a further annealing at 750 C, the unit cell of the Pt 2 Se undergoes a rotation of 30 compared with the (O3 Â O3)R30 structure at 600 C, resulting in a (2 Â 2) pattern with respect to the Pt lattice, as seen in Fig. 2e and f. For the (2 Â 2) structure, one observes a large density of defects on the surface which is consistent with the LEED pattern showing high-background and diffusing diffraction spots.…”
Section: Iii1 Leed and Stm Measurementsmentioning
confidence: 99%